74.7k views
5 votes
Solve for x: 5(x + 3) = 4(x − 3)

A. −18
B. −27
C.−3
D. −6

2 Answers

4 votes

Answer:

B

Explanation:

Given

5(x + 3) = 4(x - 3) ← distribute both sides

5x + 15 = 4x - 12 ( subtract 4x from both sides )

x + 15 = - 12 ( subtract 15 from both sides )

x = - 27 → B

User Saulotoledo
by
4.8k points
2 votes

Answer:

x=−27

Explanation:

5(x+3)=4(x−3)

Step 1: Simplify both sides of the equation.

5(x+3)=4(x−3)

(5)(x)+(5)(3)=(4)(x)+(4)(−3)(Distribute)

5x+15=4x+−12

5x+15=4x−12

Step 2: Subtract 4x from both sides.

5x+15−4x=4x−12−4x

x+15=−12

Step 3: Subtract 15 from both sides.

x+15−15=−12−15

x=−27

User Stakahop
by
4.9k points